Studi Analisis Hubungan Filsafat, Ilmu, dan Agama - Bakar, Abu; Roza, Ellya; Masduki, Masduki (ANWARUL, 2023)
Humans as God's creatures are equipped with reason and thought, with reason and mind that makes humans different from other creatures. He has a tendency to be curious about everything he sees and feels. This wish to know is accompanied by a number of questions which then become the rationale for finding answers to these questions. The series of processes that have given birth to science. Philosophy, science and religion will always color human life. The existence of philosophy, science and religion are three things that complement each other in bringing humans to the process of discovering their identity as God's creatures. Philosophy with a broad and deep reach through its contemplation must be seasoned with science so that it does not go wild in uncovering the basic assumptions that arise from a sense of humanity. To rectify these assumptions, religion is needed as a unifying pillar between science and philosophy. Philosophy without being accompanied by knowledge will only give birth to mere delusions. Knowledge that is not aligned with religion will also lead humans to a real error. Humans as creatures equipped with a perfect mind must be able to juxtapose these three things in uncovering the phenomena that occur in the natural surroundings. This paper aims to reveal the relationship between the three things mentioned above, namely philosophy, science and religion. To analyze the relationship, the authors use the method of literature review. (library research), namely a method of collecting data through sources of literature studies (readings), by recording all findings regarding the relationship between philosophy, science and religion.